Handling of Land Mafia Practices in the Ministry of ATR BPN Environment to Achieve Public Transparency - Ersoy, Muhammet Ebuzer; Wahyudi, Trubus; Polash, Humayun Kabir (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2025)
Land is a natural resource that is very important for human life. The state, as the holder of supreme power over the entire nation, is responsible for regulating the use of land to advance the prosperity of all parts of the country, as regulated in Article 33 paragraph (3) of the 1945 NRI Constitution.Legal research is conducted using the normative legal method, namely an approach to discussing by scientifically reviewing problems that are conceptualized through the description of regulations and legislation in order to produce a rule or norm. In the era of increasingly sophisticated technology in today's era, it has become something that the bureaucracy needs to try in implementing electronic certificates so that they can adapt to the future, and in implementing certificates. electronically, the government must be able to resolve the agrarian conflicts that are rife in various regions which are currently urgent. The government has created an Agrarian Reform program by issuing agrarian reform regulations. In taking action against land crimes in order to prevent and resolve conflicts, especially in law enforcement, the government should be proactive and not reactive, and the government seems to ignore issues related to land.